Kebijakan Pemerintah dan Sumber Hukum Agama, Kepercayaan, dan Adat Di Indonesia - Suyatno, Suyatno; Hartanto, Hartanto (Institut Agama Kristen Negeri Tarutung, 2025)
Government policies in Indonesia can have an impact on Indonesia's social and political dynamics regarding issues such as religious law, beliefs and customs. At the same time, the government seeks to strengthen the values of nationalism and unity. However, just as there is no ivory that is not cracked, there are still various pros and cons in the legal perspective, namely religion, beliefs, and customs as a source of law or vice versa as law by legalizing “as is” in positive law. Religion has consistently played an important role in shaping the values, ethics, and moral frameworks that support public policy, both as a source of inspiration and a source of pros and cons. This research method is normative juridical, with secondary data related to doctrines, books, laws and regulations related to government policies with correlations to religion, belief, and custom. The problem studied is how the probelmatics of government policies and legal sources of religion, belief, and custom in Indonesia. Religion in Indonesia is gradually a source of law that is accommodated in Indonesian law, one of which is in the reform of criminal law, namely Law No. 1 of 2024, but several things need attention in policy and implementation, in order to maintain equality between religious communities for the sake of unity and integrity.